The Influence of Sharia Financial Literacy, Lifestyle, and Social Media on the Consumptive Behavior of Sharia Economics Students at UINFAS Bengkulu - Wenny Marta Puspita Sari; Desi Isnaini; Debby Arisandi (Utan Kayu Publishing, 2025)
This research is conducted to examine the impact of Islamic financial literacy, lifestyle, and social media on the consumer behavior of students majoring in Islamic economics at UIN Fatmawati Soekarno Bengkulu. A quantitative method is utilized in this study, with data collected through questionnaires. The population comprises 895 individuals, and a total of 90 respondents were selected using simple random sampling based on the Slovin formula. Data analysis methods include descriptive statistical analysis, classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression, and hypothesis testing, which consists of t-tests (partial), F-tests (simultaneous), and the coefficient of determination (R²). The analysis was performed using SPSS version 26. The findings reveal that Islamic financial literacy (X1) has a positive and significant partial effect on students' consumptive behavior Likewise, lifestyle (X2) exerts a positive and statistically significant influence in a partial test, whereas social media (X3) Students’ consumptive behavior is influenced to some extent, but not entirely.